Age of the magma chamber and its physicochemical state under Elbrus Greater Caucasus, Russia using zircon petrochronology and modeling insights - Bindeman, Ilya; Melnik, O. E.; Guillong, M.; Utkin, I. S.; Wotzlaw, J.-F.; Schmitt, Axel Karl; Stern, R. A. (Scientific reports, 2023)
Mount Elbrus, Europe's tallest and largely glaciated volcano, is made of silicic lavas and is known for Holocene eruptions, but the size and state of its magma chamber remain poorly constrained. We report high spatial resolution U-Th-Pb zircon ages, co-registered with oxygen and hafnium isotopic values, span ~ 0.6 Ma in each lava, documenting magmatic initiation that forms the current edifice. The best-fit thermochemical modeling constrains magmatic fluxes at 1.2 km3/1000 year by hot (900 °C), initially zircon-undersaturated dacite into a vertically extensive magma body since ~ 0.6 Ma, whereas a volcanic episode with eruptible magma only extends over the past 0.2 Ma, matching the age of oldest lavas. Simulations explain the total magma volume of ~ 180 km3, temporally oscillating δ18O and εHf values, and a wide range of zircon age distributions in each sample. These data provide insights into the current state (~ 200 km3 of melt in a vertically extensive system) and the potential for future activity of Elbrus calling for much-needed seismic imaging. Similar zircon records worldwide require continuous intrusive activity by magmatic accretion of silicic magmas generated at depths, and that zircon ages do not reflect eruption ages but predate them by ~ 103 to 105 years reflecting protracted dissolution-crystallization histories.